Evolution of hospital discharge medication and 6 months outcomes of ST-Segment Elevation Myocardial Infarction patients in Portugal over the years. (25th November 2020) - De Sousa Bispo, J.P; Mota, T.F; Fernandes, R; Azevedo, P; Carvalho, D; Bento, D; Marques, N; Mimoso, J; Jesus, I
Abstract: Objectives: To assess the evolution of hospital discharge management, 6 months hospitalization and mortality over the years of all patients admitted with ST segment elevation myocardial infarction (STEMI) in Portugal. Methods: A nationwide electronic prospective registry that included all patients admitted to Portuguese hospitals with a diagnosis of Acute Coronary Syndrome since 2002 until 2018 was used to collect all data relative to patients admitted with a STEMI diagnosis during that time frame. Data on demographic data, clinical status, revascularization strategy, discharge medication and 6 months hospitalization and mortality were obtained. We compared the data and its evolution over the years to assess for trends. For statistical analysis, Qui-square tests were used to assess trends in categorical variables, and Kruskal-Wallis tests were used to assess trends in numerical variables. A p-value <0.05 was considered statistically significant. Results: During the study, a total of 23807 patients were admitted for STEMI in Portuguese hospitals, 74.3% were male and average age of 63.9±13.6 years. We report a progressive and significant increase the use of primary angioplasty versus fibrinolysis (24.3% to 98.4%, p<0.001), in coronary angioplasties (36.4% to 73.2%, p<0.001), in the use of drug-eluting stents (0% to 70.1%, p<0.001), and a decrease in the patients that underwent surgery (6.8% to 1.3%, p<0.001) and intra-aortic balloon pump (1.8% to 0%, p=0.009), resulting in a decrease in in-hospital mortality from 9.9% to 6.1% (p<0.001). At discharge, we report a progressive increase in the prescription of P2Y12 inhibitors (21.1% to 95.2%, p<0.001), beta-blockers (68.8% to 83.8%, p<0.001), RAAS inhibitors (69.5% to 86.7%, p<0.001) and statins (79.6% to 94.9%, p<0.001), while the prescription of aspirin (94.1% para 94.8%, p=0.428), calcium channel blockers (5.3% to 5.6%, p<0.684) stayed stable, and there was a decrease in the prescription of nitrates (52.9% to 5.8%, p<0.001). Hospital admissions at 6 months consistently and progressively reduced over time (18.6% to 8.5%, p<0.001) as well as mortality (6.7% para 4.3%, p<0.001). Conclusion: Post discharge treatment of STEMI patients in Portuguese hospitals has evolved according to guidelines, with higher prescription of medication proven to reduce outcomes, resulting in lower hospitalization rates and mortality. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Sociedade Portuguesa de Cardiologia